Effect of induction on exhaust gas recirculation and hydrogen gas in compression ignition engine with simarouba oil in dual fuel mode. (30th October 2022) - Vijayaragavan, Mathanraj; Subramanian, Balaji; Sudhakar, S.; Natrayan, L.
Abstract: Biofuels extracted from non-edible oil is sustainable and can be used as an alternative fuel for internal combustion engines. This study presents the performance, emission and combustion characteristic analysis by using simarouba oil (obtained from Simarouba seed) as an alternative fuel along with hydrogen and exhaust gas recirculation (EGR) in a compression ignition (CI) engine operating on dual fuel mode. Simarouba biofuel blend (B20) was prepared on volumetric basis by mixing simarouba oil and diesel in the proportion of 20% and 80% (v/v), respectively. Hydrogen gas was introduced at the flow rate of 2.67 kg/min, and EGR concentration was maintained at 30% of total air introduction. Performance, combustion and emission characteristics analysis were examined with biodiesel (B20), biodiesel with hydrogen substitution and biodiesel, hydrogen with EGR and were compared with neat diesel operation. Results indicate that BTE of the engine operating with biodiesel B20 was decreased when compared to neat diesel operation. However, introducing hydrogen along with B20 blend into the combustion chamber shows a slight increase in the BTE by 1%. NOx emission was increased to 18.13% with the introduction of hydrogen than that of base fuel (diesel) operation. With the introduction of EGR, there is a significant reduction in NOx emission due to decrease in in-cylinder temperature by 19.07%. A significant reduction in CO, CO2, and smoke emissions were also noted with the introduction of both hydrogen and EGR. The ignition delay and combustion duration were increased with the introduction of hydrogen, EGR with biodiesel than neat diesel operation. Hence, the proposed biodiesel B20 with H2 and EGR combination can be applied as an alternative fuel in CI engines. Highlights: Use of simarouba oil as alternative fuel in CI engine. Reduction in emissions with introduction of both hydrogen and EGR. Reduced the formation of NOx with EGR. Increase in ignition delay and combustion duration.